New species and interesting records of Spiniphallellus Bidzilya & Karsholt, 2008, from Kyrgyzstan (Lepidoptera, Gelechiidae) - Huemer, Peter; Šumpich, Jan (Zootaxa, 2025)
Spiniphallellus minimus sp. nov., a new species of the recently described gelechiid genus Spiniphallellus Bidzilya & Karsholt, 2008, is described from Kyrgyzstan. Key diagnostic characters are found in the external morphology, particularly the short forewing length, and in the male genitalia, supported by divergence in DNA barcodes. In addition, S. stonisi Bidzilya & Karsholt, 2008, previously known only from the holotype, is reported from Kyrgyzstan for the first time and redescribed, including its previously unknown female. Adults and male genitalia of both species, as well as the female genitalia of S. stonisi, are illustrated.